Performance and overview of clinically relevant areas of application of saliva testing in the cat - Schroers, Maike; Meyer-Lindenberg, Andrea (Frontiers in Veterinary Science, 2024)
The cat represents an important model in order to investigate basic physiological knowledge of salivary secretion as well as pharmacokinetics of active substances. Objective:The aim of the study was to review in which diagnostic application areas saliva testing is routinely used and in which areas it could be further explored in the future. Materials and Methods: Literature relevant to the research question was collected in March 2022 using the Pubmed database. Results: The diagnosis of infectious diseases in cat saliva is one of the most important fields of application. Saliva diagnostics may also indicate dental diseases, allergies or kidney and other metabolic diseases. Sexual and stress hormones can also be measured in cat saliva. A number of clinically relevant allergens in cat saliva that may cause allergies in humans has been investigated and described, in addition to infectious agents that can be transmitted from cats to humans. Conclusions: Saliva testing in cats can be useful in many areas, including the detection of infectious diseases, allergies and dental disease. However, it is far from being used to its full potential within veterinary medicine.